The performance of Vietnamese banking system under financial liberalization - measurement using DEA - Ngo, Dang-Thanh (Trường Đại học Kinh tế, 2016)
Using time trend data from 1990 to 2010, the research applied the efficiency measurement and Data Envelopment Analysis approach to evaluate the performance changes of Vietnamese banking system under financial liberalization. The DEA time trend model is a fruitful approach to analyze the banking sector through macro level data while banking level data is unavailable, for example the case of Vietnamese banks before 2000.